GOLUSIN-KRYLOV THEOREM FOR A(z)- ANALYTIC FUNCTION - Husenov, Behzod (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
The article explores A(z)- analytic functions. The Hardy class is given for A(z)- analytic functions is proved an analog of theorem Golusin-Krylov and Carleman’s formula is given for A(z)- analytic functions.